Matrix stiffness regulates arteriovenous differentiation of endothelial progenitor cells during vasculogenesis in nude mice. (28th November 2018) - Xue, Changyue; Huang, Qian; Zhang, Tao; Zhao, Dan; Ma, Quanquan; Tian, Taoran; Cai, Xiaoxiao
Abstract: Objectives: The aim of the study was to investigate the effect of matrix stiffness on arteriovenous differentiation of endothelial progenitor cells (EPCs) during vasculogenesis in nude mice. Materials and methods: Dextran hydrogels of differing stiffnesses were first prepared by controlling the crosslinking reaction to generate different thioether bonds. Hydrogels with stiffnesses matching those of the arterial extracellular matrix and venous extracellular matrix were separately combined with mouse bone marrow‐derived EPCs and subcutaneously implanted on either side of the backs of nude mice. After 14 days, artery‐specific marker Efnb2 and vein‐specific marker Ephb4 in the neovasculature were detected to determine the effect of matrix stiffness on the arteriovenous differentiation of EPCs in vivo. Results: Fourteen days after the implantation of the EPC‐loaded dextran hydrogels, new blood vessels were observed in both types of hydrogels. We further verified that matrix stiffness regulated the arteriovenous differentiation of EPCs during vasculogenesis via the Ras/Mek pathway. Conclusions: Matrix stiffness regulates the arteriovenous differentiation of EPCs during vasculogenesis in nude mice through the Ras/Mek pathway.